2022
DOI: 10.1093/sleep/zsac288
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of central disorders of hypersomnolence with manual and artificial-intelligence-derived polysomnographic measures

Abstract: Differentiation of central disorders of hypersomnolence (DOH) is challenging but important for patient care. This study aimed to investigate whether biomarkers derived from sleep structure evaluated both by manual scoring as well as with artificial intelligence (AI) algorithms allow distinction of patients with different DOH. We included video-polysomnography data of 40 narcolepsy type 1 (NT1), 26 narcolepsy type 2 (NT2), 23 idiopathic hypersomnia (IH) patients and 54 subjects with subjective excessive daytime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Table 2 summarizes the kappa values for the 20 validation studies of the 6 AI-based autoscoring algorithms outputting the hypnodensity graph (Stephansen et al, 2018;Cesari et al, 2021Cesari et al, , 2022Vallat and Walker, 2021;Anderer et al, 2022b;Brandmayr et al, 2022;Bakker et al, 2023;Fiorillo et al, 2023b). As can be seen in Table 2, Cohen's kappa for the 5-stage comparison was comparable between the six algorithms.…”
Section: Hypnodensity-derived Sleep Stages and Parametersmentioning
confidence: 93%
See 4 more Smart Citations
“…Table 2 summarizes the kappa values for the 20 validation studies of the 6 AI-based autoscoring algorithms outputting the hypnodensity graph (Stephansen et al, 2018;Cesari et al, 2021Cesari et al, , 2022Vallat and Walker, 2021;Anderer et al, 2022b;Brandmayr et al, 2022;Bakker et al, 2023;Fiorillo et al, 2023b). As can be seen in Table 2, Cohen's kappa for the 5-stage comparison was comparable between the six algorithms.…”
Section: Hypnodensity-derived Sleep Stages and Parametersmentioning
confidence: 93%
“…Stephansen et al (2018), Bakker et al (2023) and Fiorillo et al (2023b) validated their algorithms in the same IS-RC cohort and reported, as compared to the consensus of 6 scorers, kappa values between 0.67 and 0.78. Cesari et al (2022) compared the Stanford-STAGES and YASA algorithm in a dataset of patients with central disorders of hypersomnolence and reported almost identical kappa values for the two algorithms (0.747 and 0.755 for Stanford-STAGES and YASA, respectively). These findings suggest that modern AI-based autoscoring systems offer valid alternatives to manual expert scoring and that the role of manual adjustment and expert review of automatic scorings might no longer be required.…”
Section: Hypnodensity-derived Sleep Stages and Parametersmentioning
confidence: 98%
See 3 more Smart Citations